THE MAIN CHARACTER’S DEVELOPMENT IN MANGA HELL’S PARADISE: JIGOKURAKU BY YUJI KAKU: A FREUDIAN PSYCHOANALYSIS - Armando, Michael; Pandin, Moses Glorino Rumambo; Datau, Rizal Octofianto (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This research aims to analyze the psychological development of the main character "Gabimaru" in Yūji Kaku's Hell's Paradise: Jigokuraku. The focus is on how Gabimaru copes with past trauma and manages his id, ego, and superego in the present. The writer is collecting and determining this study through a qualitative descriptive method that includes both conversation and visuals from the manga Hell's Paradise: Jigokuraku.